(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The Island of Chios (northern Egean Sea, Greece) is known for a well-preserved Paleozoic to Mesozoic sedimentary sequence. This paper is focused on the micropaleontology and biostratigraphy of the Marmarotrapeza Formation (Lower/Middle Triassic) and of the overlying Bunte Serie Unit (Middle Triassic), outcropping near the Marathovouno Hillock section proposed by Assereto (1974) as type-section for the Aegean substage (Lower Anisian). The results obtained allow to better define the age of the Bunte Serie basin and of the coeval carbonate platform, which ranges from the Anisian (?Pelsonian) to the Norian-?Rhaetian.